2012
DOI: 10.1007/s00431-012-1874-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and oral health-related behaviour in preschool children: evidence for a social gradient

Abstract: Abstract.This study aims to investigate the social gradient in the reported oral health-related behaviour and oral health status of preschool children. Participants were 1,057 children born between October 2003 and July 2004 in Flanders, Belgium. Oral health examinations were performed by trained dentists when the children were three and five years old (respectively in 2007 and 2009); data on dietary habits, oral hygiene habits and dental attendance of the children were obtained through structured questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
3
22
0
3
Order By: Relevance
“…Most studies only took the educational level of mothers into account [18,20,23]. Interestingly, an increased risk of caries was associated not only with low educational levels of mothers but also even with their high acquisition of university degrees [36]. We found that even when parents have a higher scholarly education level, migration background has an association with DMFT values.…”
Section: Discussionmentioning
confidence: 57%
“…Most studies only took the educational level of mothers into account [18,20,23]. Interestingly, an increased risk of caries was associated not only with low educational levels of mothers but also even with their high acquisition of university degrees [36]. We found that even when parents have a higher scholarly education level, migration background has an association with DMFT values.…”
Section: Discussionmentioning
confidence: 57%
“…Parents/caregivers with a low level of education and lower household income were associated with cavitated lesions in the children of this study. These individual socioeconomic determinants may reflect less access to information and less acquisitive power for the employment of healthy behaviors. Such differences indicate the influence of socioeconomic factors on oral hygiene habits and access to healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Bireyi etkilemek, toplumsal ve kültürel faktörler dâhilinde oral hijyen alışkanlıklarını şekillendirmek zor olabilmektedir. 72 Ancak, toplum temelli eğitim programları ve uygulamaları ile ağız sağlığı konusunda toplumsal bilinçlenme ve doğru tutum ve davranış oluşturmak, acil ağız ve diş sağ-lığı hizmetlerine ihtiyacın azalmasını sağlayarak sağlıklı nesiller yetişmesine yardımcı olacaktır. 73,74 Koruyucu ağız ve diş sağlığı önemi hakkında geliştirilmiş halk eğitiminin, doğum öncesi ebeveynlik eğitiminin devam eden bir parçası olması, küçük çocukların velileriyle iletişim kurulduğunda öncelikli olarak; şekerli içeceklerin tüketi-minin azaltılması, biberonla içilen sıvılara özellikle geceleri şeker ilave edilmemesi ve doğumdan itibaren başlanmak üzere bebeğin diş etlerinin yumuşak bir fırça veya temiz, nemli bir bez parçasıyla temizlenmesi hakkında bilgiler verilmesi, çocukların ömür boyu sağlıklı oral hijyen alışkanlıkları kazanmasına yardımcı olacaktır.…”
Section: Eçç'ni̇n öNlenmesi̇nde Toplum Temelli̇ Eği̇ti̇munclassified